Pengaruh Kredibilitas, Reputasi, Dan Kemampuan Persuasif Food Bloggers Terhadap Intensi Konsumen Dalam Memilih Sebuah Restoran - Audina, Melly (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The impact of globalization has affected many aspects in the development of human life. Over time, the internet has become one of the human needs to survive in this era of globalization. The use of the internet in the world of marketing is not a taboo thing for the people of Indonesia, especially Jakarta. This study aims to determine the effect of reputation, credibility, and persuasive ability of each or simultaneously on the intensity of consumers in choosing a restaurant. The research methodology used is in the form of a quantitative test carried out by distributing questionnaires to 148 respondents and analyzed by SPSS Statistics 22 application. The results of the analysis show that all variables are declared valid and reliable. The credibility variable is considered to have a significant influence on the intention of choosing a restaurant. Reputable variables do not have a significant effect on the selection of a restaurant because the established and strong restaurant names are not affected by the reputation of endorsers. The variable persuasive ability has a significant influence on the selection of a restaurant. Variables of credibility, reputation, and persuasive abilities of food bloggers have a close relationship with consumer purchasing decisions.